International Higher Education policy research and management forum 2006. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
The “International Higher Education Policy Research and Management Forum 2006” was successfully organised by the National Higher Education Research Institute (IPPTN) and Universiti Sains Malaysia (USM), with the cooperation of the Ministry of Higher Education Malaysia and the Centre for Asia Pacific Social Transformation Studies (CAPSTRANS), University of Wollongong, Australia.